Enhanced electrochemical properties of lithium cobalt titanate via lithium-site substitution with sodium. (20th August 2015) - Chen, Wei; Liang, Hangfeng; Qi, Zhengbing; Shao, Lianyi; Shu, Jie; Wang, Zhoucheng
Graphical abstract: Highlights: A series of Li2−x Nax CoTi3 O8 is prepared for the first time by solid state route. Na-doping improves the lithium ion diffusion coefficient within Li2 CoTi3 O8 . Na-doping changes the disorder degree of cation locations in the structure. Li1.90 Na0.10 CoTi3 O8 shows the best electrochemical property. Reversible structural evolution of Li1.90 Na0.10 CoTi3 O8 is proved by in-situ XRD. Abstract: Na-doped Li2 CoTi3 O8 is prepared via Li-site substitution with Na for the purpose of improving its cycle performance as an anode. Upon Na-doping, Rietveld refinement result reveals that Na takes the tetrahedral sites (8c) shared with Li and Co in the structure. Due to the larger ionic radius of Na than Li, an increased disorder degree of ion locations in the structure is induced by Na doping. Furthermore, the lithium ion diffusion tunnel is also expanded after Na doping. Galvanostatic charge/discharge tests denote that Li1.90 Na0.10 CoTi3 O8 displays better cycling property and higher reversible capacity than pristine Li2 CoTi3 O8 and other Li2−x Nax CoTi3 O8 materials. It can be found that Li1.90 Na0.10 CoTi3 O8 can maintain a reversible capacity of 268.9 mAh g −1 at a current density of 100 mA g −1 (0.14 C) after 50 cycles, corresponding to 90.6% of the initial charge capacity. Even cycled at a high current density of 1426 mA g −1 (2 C), Li1.90 Na0.10 CoTi3 O8 can also maintain a reversible capacity of 179.2 mAh g −1 after 80 cycles. Besides, the reversible structural changes of Na-doped Li2 CoTi3 O8 are also proved by various in-situ and ex-situ observations. The significant improvements at cycling and rate performances demonstrate that Li1.90 Na0.10 CoTi3 O8 is a promising anode material for rechargeable lithium-ion batteries.